2009
DOI: 10.1177/1049731508329385
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Wraparound Services for Severely Emotionally Disturbed Youths

Abstract: Objectives: Services to children and adolescents with a severe emotional disturbance (SED) have long been inadequate. The wraparound approach has emerged as a promising practice that could address the needs of children with SED and their families through a strength-based, individualized, family-focused team process that emphasizes flexible service planning. This study compares the outcomes of youth receiving the wraparound approach with youth receiving traditional child welfare case management. Method: Child b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…This finding suggests that when the child does not receive services and only the caregiver living in adverse community conditions utilizes services for physical, psychological, or substance abuse problems, unfavorable, and yet unknown, interpersonal mechanisms that lead to the child's maltreatment are sustained and reacted to by the child resulting in increased externalizing problems, such as hyperactive, delinquent, antisocial, and aggressive behaviors (Duhig et al 2000). This finding may suggest that caregiver and child services are required concurrently, or that family treatment is a necessary additional component to caregiver service use (Mears et al 2009). These wraparound services, however, may be unavailable to families who live in communities characterized by poverty and adverse conditions (Weiner et al 2011).…”
Section: Implications For Practice Policy and Future Researchmentioning
confidence: 94%
“…This finding suggests that when the child does not receive services and only the caregiver living in adverse community conditions utilizes services for physical, psychological, or substance abuse problems, unfavorable, and yet unknown, interpersonal mechanisms that lead to the child's maltreatment are sustained and reacted to by the child resulting in increased externalizing problems, such as hyperactive, delinquent, antisocial, and aggressive behaviors (Duhig et al 2000). This finding may suggest that caregiver and child services are required concurrently, or that family treatment is a necessary additional component to caregiver service use (Mears et al 2009). These wraparound services, however, may be unavailable to families who live in communities characterized by poverty and adverse conditions (Weiner et al 2011).…”
Section: Implications For Practice Policy and Future Researchmentioning
confidence: 94%
“…This analysis reviewed seven studies that utilized random assignment or a comparison group. Of the seven studies, four were conducted with a child welfare population (Bruns et al 2006a;Clark et al 1998;Mears et al 2009;Rauso et al 2009); two with a juvenile justice population (Carney and Buttell 2003;Pullmann et al 2006); and three with a mental health population (Evans et al 1996;Hyde et al 1996;Myaard et al 2000). Overall, the findings of the review were favorable for wraparound; noting small to medium effects in the areas of improved youth functioning, youth behavior problems, living situations, and community adjustment.…”
Section: Empirical Review Of Wraparoundmentioning
confidence: 79%
“…The findings of these later studies, which will be reviewed here, are mixed on the benefits of wraparound. Four studies reported in the literature found youth receiving wraparound services to have better outcomes than youth receiving usual services (Anderson et al 2008;Bruns et al 2006a;Mears et al 2009;Rauso et al 2009). The first of these studies (Bruns et al 2006a) utilized a quasi-experimental design to compare wraparound to usual services (traditional case management) for youth with SED in the foster care system across 4 different regions of Nevada.…”
Section: Empirical Review Of Wraparoundmentioning
confidence: 93%
See 1 more Smart Citation
“…Analyses of the 585 responses showed good reliability and validity for the PPFT, indicating that it is a psychometrically sound tool. KEY WORDS: model fidelity; parent partner; validation study; Wraparound W raparound, a comprehensive, teambased focus for engaging families with youths with emotional or behavioral disabilities who are in higher levels of out-of-home care, is one of the most important approaches to strengthening families that has been introduced in systems that serve families (Bruns, Burchard, Suter, Leverentz-Brady, & Force, 2004;Mears, Yaffe, & Harris, 2009;Walker & Bruns, 2006a, 2006b). Wraparound helps families prepare for the emancipation or return home of the youth.…”
mentioning
confidence: 99%